Atlas moth (Attacus atlas Linnaeus, 1758) silk sericin protein: The effect of extraction methods and storage time on its content - Hipny Alwandri; Sukirno Sukirno; Siti Sumarmi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.